Penyuluhan Edukasi Kesehatan Reproduksi Remaja Dalam Upaya Pencegahan Anemia SMP Al-Azhar - Dila Diwani; Dinda Maulida Nur; M Farouq Al-Azid; Nazua Nabila; Nur Delina Sinambela; Nur Elviyani Sinaga; Putri Cahya Wulandari; Riska Fadilla Pasaribu; Siti Sarah Berutu; Suzani Adina (Alahyan Jurnal Pengabdian Masyarakat Multidisiplin, 2023)
Anemia is a micronutrient problem that occurs throughout the world, especially in developing countries which is estimated to occur in 30% of the world's population. As a result, lack of hemoglobin levels causes symptoms of lethargy, weakness, fatigue, and fatigue when doing activities that will have an impact on decreasing concentration and learning achievement, and in the long term will have an impact on the quality of human resources, where adolescents are the future generation of the nation who will later support determining the next generation. Adolescence is where the transition phase occurs or the transition period from children to adults. Characterized by various changes such as physical, mindset, and social changes in life. But among adolescents anemia is not unfamiliar, this disease is related to insufficient nutritional intake that adversely affects adolescent health. So it is necessary to inform all adolescents that anemia is a serious disease that needs attention. Thus, this study is to analyze the understanding of adolescents related to anemia after and before giving questionnaires. So it is proven that after being given a questionnaire in the form of a statement about anemia, it can be understood by respondents significantly.